Credibility of sustainability reports: The contribution of audit committees. (28th February 2018) - Al‐Shaer, Habiba; Zaman, Mahbub
Abstract: Concerns about the credibility of sustainability reports can be mitigated through assurance. Although audit committee remit encompasses monitoring of sustainability issues, there are potential complementary and substitution issues between governance mechanisms. This paper explores the relationship between audit committees and sustainability reporting assurance using resource dependency theory. We find audit committee characteristics have an impact, additional to that of the board of directors and the existence of sustainability committees, on voluntary sustainability assurance. Our results also show that audit committee independence is associated with use of a Big Four audit firm for sustainability assurance. A negative association between sustainability committees and assurance, however, indicates assurance could be a burden for small firms. Overall, the findings suggest audit committees add credibility and help improve sustainability reporting through their independence, expertise and oversight.